Child Grooming (Technology-Based Sexual Harassment) in the Context of Indonesian Law - Mandriyani, Sulvy; Wahyuningtyas, Nanda Tri; Haikal, Muhammad Fikri; Ifrani, Ifrani (International Journal of Law, Environment, and Natural Resources, 2024)
Child grooming is a form of sexual harassment that continues to develop because sexual harassment is often carried out directly by the perpetrator, and is often carried out through social media. The perpetrator manipulates Child Grooming by being kind and attentive so that the child believes that the person he has just met is a good person. In Indonesia, Child Grooming is a new type of crime, and is based on existing regulations. The method used in this study is normative legal research. The approach in the research utilizes a legislative approach. The legal materials used in this study are primary legal materials, secondary legal materials, and tertiary legal materials. In the normative law research that is being carried out, the data collection method is by conducting a bibliographic study. The act of Child Grooming is a form of sexual crime that uses minors as targets. Although the Child Protection Law has regulated the protection of children, the existing articles are still limited in regulating obscene acts in general. And in the regulations in Indonesia there are 10 rules or articles that can be imposed on Child Grooming perpetrators.